2018
DOI: 10.1007/s00415-018-9008-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic power of CSF Tau in amyotrophic lateral sclerosis

Abstract: CSF t-Tau showed no reliable diagnostic significance but the relation between the high levels of CSF t-Tau and short survival suggests the potential prognostic role of this biomarker in ALS. However, CSF NFL was confirmed to be the most reliable and efficient tool for diagnosis and prediction of clinical progression and survival in ALS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 40 publications
11
45
1
Order By: Relevance
“…Conversely, another study showed that elevated levels of Aβ1-42 were associated with shorter survival [26]. A previous study found that total Tau was associated with shorter survival and higher progression rate, but not with ASLFRS-R [15]. Our study also reinforces previous findings showing that levels of total Tau, phospho-Tau, or the phospho-Tau/total Tau ratio were not correlated with survival [27].…”
Section: Mild Prognosis Role Of Phospho-tau and Total Tau In Alssupporting
confidence: 85%
See 1 more Smart Citation
“…Conversely, another study showed that elevated levels of Aβ1-42 were associated with shorter survival [26]. A previous study found that total Tau was associated with shorter survival and higher progression rate, but not with ASLFRS-R [15]. Our study also reinforces previous findings showing that levels of total Tau, phospho-Tau, or the phospho-Tau/total Tau ratio were not correlated with survival [27].…”
Section: Mild Prognosis Role Of Phospho-tau and Total Tau In Alssupporting
confidence: 85%
“…Phosphorylated-Tau protein is associated with the pathophysiology of Alzheimer's disease (AD), and is increased in AD as well [4][5][6][7]. In ALS, studies report opposite results [8][9][10][11][12], and some groups suggest that levels of CSF Tau at baseline could be correlated with disease progression [13][14][15]. Moreover, alterations in the amyloid processing protein (APP) and amyloid β1-42 peptide have been shown in the CSF and spinal cord of ALS patients [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen studies investigated CSF NfL concentration in 930 ALS cases compared with 593 cognitively unimpaired controls [4,27,34,41,[57][58][59][64][65][66][67][68][69][70][71], with an average CSF NfL concentration ratio of 9.64 (95% CI 6.65-13.99, P , 0.0001; Fig. 4A).…”
Section: Nfl In Alsmentioning
confidence: 99%
“…In addition, 11 studies investigated CSF NfL concentration of 1239 ALS cases compared with 806 disease mimic controls, with an average concentration ratio of 3.35 (95% CI 2.19-5.12, P , 0.0001; Fig. 4B) [4,8,27,57,65,68,69,[72][73][74][75].…”
Section: Nfl In Alsmentioning
confidence: 99%
“…Disruption of neurofilament organisation is one of the key characteristics of many neurological conditions, such as amyotrophic lateral sclerosis (ALS), AD, FTD or vascular dementia among others 6,9,10 . In addition, recent studies have shown that levels of NfL in CSF are associated with clinical progression and severity in ALS [11][12][13] and in other neurodegenerative diseases due to its capacity to reflect the extent of neuro-axonal damage 14,15 . Recently, a large control-case study that included various neurodegenerative disorders confimed the importance of CSF NfL in the evaluation and follow-up of patients with cognitive impairment 16 : in particular, CSF NfL levels were increased in patients with a diagnosis of MCI, AD, FTD or ALS compared to controls, thus reflecting the intensity of neurodegenerative processes.…”
mentioning
confidence: 99%